Analisis Keagamaan Minoritas Muslim Di Kalangan Mayoritas Kristen Di Desa Manuk Mulia, Kecamatan Tigapanah, Kabupaten Karo - Dalimunthe, Muhammad Fitrah; Nasution, Muhammad Ali Azmi (Kamaya: Jurnal Ilmu Agama, 2024)
Indonesia with its rich religious diversity, presents unique challenges in understanding social and religious dynamics, particularly regarding the interaction between Muslim and Christian communities in different regions. One interesting phenomenon is in Manuk Mulia Village, Tigapanah Sub-district, Karo Regency, where the majority of the population is Christian while a small minority is Muslim. This study aims to analyse the role, challenges and factors that influence the religious identity of the Muslim minority amidst the Christian majority. Using a qualitative approach through in-depth interviews and participatory observation, the results show that Muslim minorities face challenges in carrying out worship and religious activities due to unequal access to facilities, social stigma, and cultural pressure. However, they remain active in strengthening solidarity by organising regular recitations as an effort to maintain religious identity. Despite significant religious differences, the people of Manuk Mulia Village live in harmony and respect each other by attending each group's religious and cultural events. This research provides an in-depth understanding of the conditions of religious minorities, the dynamics of interfaith relations, and the implications for tolerance and harmony in religiously diverse rural communities.